Implementation of more sensitive cardiac troponin T assay in a state-wide health service. (15th January 2022) - Khan, Ehsan; Lambrakis, Kristina; Nazir, Sheraz A.; Chuang, Anthony; Halabi, Amera; Tiver, Kathryn; Briffa, Tom; Cullen, Louise A.; Horsfall, Matthew; French, John K.; Sun, Benjamin C.; Chew, Derek P.
Abstract: Aims: Explore the impact of deploying high-sensitivity (hs) cardiac troponin T (cTnT) assay across a state-wide health service. Methods and results: Presentations to emergency departments of six tertiary hospitals between January 2008 and August 2019 were included; standard cTnT assay was superseded by hs-cTnT in June 2011 without changing the reference range (≥30 ng/L reported as elevated), despite cTnT level of 30 ng/L being equivalent to ∼44 ng/L with hs-cTnT. Clinical outcomes were captured using state-wide linked health records. Interrupted time series analyses were used adjusted for seasonality and multiple co-morbidities using propensity score matching allowing for correlation within hospitals. In total, 614, 847 presentations had ≥1 troponin measurement. Clinical ordering of troponin decreased throughout the study with no increase in elevated measurements amongst those tested with hs-cTnT. Small but statistically significant changes in index myocardial infarction (MI) diagnosis (−0.36%/year, 95%CI [confidence interval]:–0.48, −0.24, p < 0.001) and invasive coronary angiography (0.12%/year, 95%CI:0, 0.24, p = 0.02) were seen, with no impact on death/MI at 30 days or 3-year survival in episodes of care (EOCs) with elevated cTnT after hs-cTnT implementation. Length of stay (LOS) was shorter among those with an elevated hs-cTnT (−4.44 h/year, 95%CI:–5.27, −3.60, p < 0.001). Non-elevated cTnT EOCs demonstrated shorter total LOS and improved 3-year survival (adjusted hazard ratio:0.90, 95%CI:0.83, 0.97, p = 0.008) although death/MI at 30 days was unchanged using hs-cTnT. Conclusion: Widespread implementation of hs-cTnT without altering clinical thresholds reported to clinicians provided significantly shorter LOS without a clinically significant impact on clinical outcomes. A safer cohort with non-elevated cTnT was identified by hs-cTnT compared to the standard cTnT assay. Highlights: hs-cTnT implementation reduced LOS without clinically significant impact on outcomes. hs-cTnT identified a safer non-elevated cTnT cohort compared to the standard assay. Progressively increasing hs-cTnT reporting threshold increases risk of late outcomes. Future RCTs are required to establish if late outcomes in low cTn elevation are avoidable.